Advanced International Experiences in Managing Non-Performing Loans in Commercial Banks (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This research article examines the strategies and approaches employed by commercial banks worldwide to manage non-performing loans (NPLs), focusing on restructuring, asset selling, legal approaches, and debt management services. Utilizing data and examples from multiple countries, the article highlights the significance of effective NPL management in maintaining financial stability and reputation. Additionally, it explores the impact of macroeconomic indicators and governance on the performance of bank loans, drawing on empirical models and data from 53 African countries between 2005 and 2021.